Improvement of spring canola Brassica napus by use of winter canola (Journal of Oilseed Brassica, 2026)
Further improving of seed yield, other agronomic and seed quality traits in spring canola Brassica napus requires broadening of genetic diversity in this crop. The European winter oilseed B. napus is known to be genetically diverse from spring oilseed B. napus. We hypothesized that elite spring canola B. napus lines with greater seed yield and genetic diversity can be achieved through the use of European winter B. napus. For this, a winter x spring B. napus breeding program was undertaken at the University of Alberta, and pedigree and doubled haploid breeding techniques were applied. Spring canola lines with significantly increased seed yield were obtained in one cycle of breeding. Estimates of genetic diversity based on SSR markers revealed that some of the spring canola lines derived from winter x spring crosses possess greater diversity compared to the spring parents. The major constraint of this winter x spring breeding is that lateness of flowering and maturity are generally introduced into the spring type lines which would require repeated cycle of breeding for improvement.